Processing Technology of Ketupat - Isnaini Rahmadi (Perum BULOG, 2019)
Indonesia has a typical rice processing method as part of the nation’s culture, namely ketupat. Ketupat is typical food made of rice wrapped in diamond shaped-woven coconut leaves and boiled in water. This article reviewed the variety of processing ketupat as well as changes in ketupat during storage of ketupat according to the results of research and related references. Traditionally, ketupat is cooked in boiling water for 5 hours. This is considered inefficient in terms of cooking fuel and time required for cooking. The efforts of modifying ketupat cooking method have been done to shorten processing time, such as cooking ketupat in pressure cooker for 30 minutes. The development of ready-to-cook ketupat or quick-cooking product in attractive package becomes a promising opportunity. Quick-cooking ketupat was made by immersing ketupat in salt, steaming, freezing and drying. The package of quick-cooking ketupat was designed using HDPE plastics made square shape that requires boiling period for 30 minutes. Ingredients and the amount of rice, the size of coconut leaves, immersion process and cooking technic affected the texture of ketupat produced. Ketupat is normally stored for 2 days in room temperature and 4-7 day if it is refrigerated. Spoilage of ketupat is due to microbiological and physical changes during storage. Starch retrogradation and increase in RS III may occur when ketupat is stored at low temperature.